2022
DOI: 10.3390/nu14061291
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Nontranscriptional Effects of Calcifediol and Calcitriol

Abstract: Classically, a secosteroid hormone, vitamin D, has been implicated in calcium and phosphate homeostasis and has been associated with the pathogenesis of rickets and osteomalacia in patients with severe nutritional vitamin D deficiency. The spectrum of known vitamin D-mediated effects has been expanded in recent years. However, the mechanisms of how exactly this hormone elicits its biological function are still not fully understood. The interaction of this metabolite with the vitamin D receptor (VDR) and, subse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 73 publications
1
23
0
Order By: Relevance
“…Lockdowns and curfews lowered mean serum 25(OH)D concentration, thus, significantly increasing the invulnerability to the SARS-CoV-2 virus, its complications, and deaths [ 26 , 27 ]. Nutritional status is one of the critical aspects responsible for overall health and well-being, including maintaining proper immune system functioning [ 17 , 28 ]. In addition to vitamin D, other essential micronutrients, such as zinc, magnesium, omega-3 fatty acids, quercetin, etc., are also necessary to optimise the functions of the endocrine system.…”
Section: Vitamin D—serum 25(oh)d Concentrations Necessary To Overcome...mentioning
confidence: 99%
See 1 more Smart Citation
“…Lockdowns and curfews lowered mean serum 25(OH)D concentration, thus, significantly increasing the invulnerability to the SARS-CoV-2 virus, its complications, and deaths [ 26 , 27 ]. Nutritional status is one of the critical aspects responsible for overall health and well-being, including maintaining proper immune system functioning [ 17 , 28 ]. In addition to vitamin D, other essential micronutrients, such as zinc, magnesium, omega-3 fatty acids, quercetin, etc., are also necessary to optimise the functions of the endocrine system.…”
Section: Vitamin D—serum 25(oh)d Concentrations Necessary To Overcome...mentioning
confidence: 99%
“…These explain the non-involvement of the genomic mechanisms of the rapid action of lipid-soluble steroid hormones [ 3 ]. The cubilin-mediated endocytosis of vitamin D is another example of vitamin D membrane–receptor-associated rapid actions of vitamin D. The article by Donate et al, 2022 describes several non-genomic rapid actions of vitamin D [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…No significant alterations in transcriptional expression levels of pdia3 were observed in the hepatic tissue of our vdra -/-;vdrb -/fish (data not shown). However, the majority of the responses mediated by vitamin D 3 non-genomic signaling have implicated post-translational modification (24,26,27). It has been reported that pdia3 might have a significant role in calcium absorption, skeletal development, lipogenesis, and insulin regulation (24)(25)(26)(27).…”
Section: A B D E Cmentioning
confidence: 99%
“…However, the majority of the responses mediated by vitamin D 3 non-genomic signaling have implicated post-translational modification (24,26,27). It has been reported that pdia3 might have a significant role in calcium absorption, skeletal development, lipogenesis, and insulin regulation (24)(25)(26)(27).…”
Section: A B D E Cmentioning
confidence: 99%
“…However, PDIA3 was also shown to participate in cells’ protection against the formation of thymine dimers after irradiation with UV [ 122 ]. The effect was associated with activation of PKC signaling and calcium influx [ 180 ]. In addition, 1,25(OH) 2 D 3 protected cells from UVR-induced thymine dimers via stimulation of chloride currents [ 144 ].…”
Section: Is Vitamin D As a Scavenger Of Free Radicals Or Their Source?mentioning
confidence: 99%